A Novel Technique to Investigate the Role of Traps in the Off‐State Performance of AlGaN/GaN High Electron Mobility Transistor on Si Using Substrate Bias. Issue 7 (29th December 2019) - Remesh, Nayana; Kumar, Sandeep; Guiney, Ivor; Humphreys, Colin J.; Raghavan, Srinivasan; Muralidharan, Rangarajan; Nath, Digbijoy N.
Abstract : Leakage mediated by GaN buffer traps is identified and studied using a novel characterization technique. Through back‐gating measurement, the effect of buffer trap states on the lateral leakage is determined by probing mesa‐isolated Ohmic pads. Time‐dependent leakage measurements are carried out to study the extent of the increase in buffer leakage due to the traps. It is observed that the mesa leakage is more prominent at very slow sweep rates and high substrate bias. The temperature‐dependent measurements show that the mesa leakage and the substrate leakage are characterized by thermionic emission from the traps with an activation barrier of 0.34 and 0.2 eV, respectively. Abstract : A novel characterization technique to study trap mediated the buffer leakage in GaN layer is reported. Through back gating measurement, effect of buffer trap states on the lateral leakage is determined by probing mesa isolated Ohmic pads. The temperature‐dependent leakage measurements carried out on the samples revealed that the leakage is predominantly due to thermionic emission from the buffer traps.